Mission in the age of digitization - Sidianto, Daniel; Simanjuntak, Ferry; Prihanto, Joko (Sekola Tinggi Teologi Sangkakala Jakarta, 2023)
ABSTRACT At this time humans are entering a new phase, where the digital world, namely virtual technology can connect humans without being hindered by location, conditions and time. There is an essential difference between the Church's three tasks running analogously compared to the digital version of worship. The digital world is not the real world, but evangelism must still be carried out according to the Great Commission of Jesus (Matthew 28:19-20). The methodology begins with the elaboration of the meaning of the three tasks of the Church, namely: koinonia, diakonia and marturia. Then make a comparison between the three tasks of the Church and the mission that occurs in the digital world and the metaverse. the conclusion is: the target of evangelism is discipleship and all services in the digital world must end by bringing it into the real world so that the essence of the Church's task, namely koinonia, diakonia and marturia, is in accordance with the biblical concept. This research is different from previous studies. The emphasis is on the spread of evangelistic missions in the digital world seen and reviewed and a comparison of the three tasks of the Church of koinonia, diakonia and marturia is a new research. Keywords: Digital world, Metaverse, Evangelism, Mission. ABSTRAK Pada masa sekarang ini manusia memasuki babak baru, dimana dunia digital, yaitu teknologi virtual dapat menghubungkan manusia tanpa terhalang dengan lokasi, kondisi dan waktu. Ada perbedaan esensial antara tiga tugas Gereja yang berjalan secara analog dibanding dengan ibadah versi digital. Dunia digital memang bukanlah dunia sesungguhnya, namun penginjilan tetap harus dilakukan sesuai Amanat Agung Yesus (Matius 28:19-20). Metodologi dimulai dengan penjabaran makna tiga tugas Gereja yaitu: koinonia, diakonia dan marturia. Kemudian membuat komparasi antara tiga tugas Gereja dengan misi yang terjadi di dunia digital dan metaverse. Kesimpulan yang dihasilkan adalah: target penginjilan adalah pemuridan dan semua pelayanan di dunia digital harus berujung dengan membawanya ke dunia nyata sehingga esensi tugas Gereja yaitu koinonia, diakonia dan marturia sesuai dengan konsep Alkitabiah. Penelitian ini berbeda dibanding dengan penelitian-penelitian sebelumnya. Penekanannya adalah penyebaran misi penginjilan di dunia digital dipandang dan ditinjau serta dikomparasi dari tiga tugas Gereja koinonia, diakonia dan marturia merupakan penelitian baru. Kata kunci: Dunia digital, Metaverse, Penginjilan, Misi.